Strategy of the sour cherry verticum in the Northern Great Plain Region Hungary (Analytic study) - Nyéki, J.; Soltész, M.; Popovics, L.; Szabó, T.; Thurzó, S.; Holb, I. J.; Fári, M. G.; Veres, Zs.; Harsányi, G.; Szabó, Z. (International Journal of Horticultural Science, 2005)
Sour cherry growing and consumption grows dynamically around the world. The present volume of 1 million tons will incerase within 10 years with 20-30, or even with 50%. In the world wide sour cherry production, Europe is a decisive factor, i.e. 2/3 of the volume is grown there. Prominent capacities are concentrated in East-Central Europe, mainly Poland, Germany and Hungary. In the future, new concurrent exporters are expected on the European market as Turkey, Iran, Serbia-Montenegro. Hungarian sour cherry production has rich traditions, so the growing techniques and the assortment of sour cherry varieties make Hungary a „Great Power" on this field. Fresh fruit and products developed from sour cherry represent values distinguished as „Hungaricum" on the markets. Sour cherry growing and the path of its products are one of the „pulling branches" of Hungarian fruit growing. Sour cherry occupies 15% of area for fruit growing and 40% within the stone fruits. Sour cherry was grown widely in Hungary, it was grown everywhere as for utilizing waste areas. This is the main reason that yields are low as a mean of 15 000 ha and the volume is low (50-60 000 tons) only. To that poor figure the heavy infections of Monilia contributed substantially in the last couple of years. The two most valid arguments of using the present varieties as the best solution are 1) the cross bred new varieties, and 2) the selections of local, traditional varieties, which substituted the earlier dominant 'Pándy meggy' variety, which had a good quality but yielded poorly. Sour cherry growing of Hungary shifted from the dry regions of the country toward the cooler and more humid regions, where the weather excesses secure a less risky production. The most decisive region is the Norther Great Plain Region comprising SzabolcsSzatmar-Bereg county, where more than the half of the Hungarian sour cherry volume is produced, and which is bound to increase its production in the future. The majority of sour cherry produced in Hungary is processed, moreover, an important fraction of the exported fresh fruit is also used by the industry. The main importer of Hungarian sour cherry is Germany. The industry manufactures mainly canned products, a smaller fraction will be processed to other products. The expected volumes of sour cherry grown in Hungary in the next 5 and 10-year-period was estimated from data based on the ratio of young plantations, predicted consequences of the global climatic changes, phytosanitary aspects, furthermore, on the development of the technological level. In the region, the volume grown within 5 years, 40 000 t/year will increase within 10 years to 55 000 t/y. The processing in Hungary is not sufficiently differenciated, which is attributed partly to the characters of the varieties, partly to the weaknesses of the processing industry. One of the reasons is the suitability of varieties mainly for canning products. Processed sour cherry products could not be sold at the same price levels achieved by concurrent sour cherry growing countries. The vertical structure of the path of products of sour cherry disposes of adequate processing capacity being ready to be developed or there is sufficient intention of making investments for the purpose of manufacturing special sour cherry products. Significant tasks of development are actual in the field of the ecological and biological conditions of production. Volume and yield security as well as the maturity time and diversification of processing possibilities are the main endeavours in widening the assortment of varieties to be grown in the near future. The main objective in growing techniques is the modernization of phytotechnical procedures, and new solutions of methods of mechanical harvesting and related technical innovations are necessary in the sour cherry verticum. A key question is the effectiveness of phytosanitary procedures with special reference to the Monilia fungus and to the cherry fruit fly as the most important pest. There are two points of break through in the Hungarian sour cherry verticum. On the one hand, meeting the increasing demands in fuits for fresh consumption, on the other hand, the diversification of processed sour cherry products and their introduction to the markets. Both are aiming to increase the competitiveness of the Hungarian sour cherry. For that purpose, outstanding varieties and excellent as well as internationally recognised fruit qualities are ready to be utilized. The most susceptible problems of the Hungarian sour cherry verticum are associated with marketing, alliance of the grower-and processor organisations and their co-operation because no overall integration within the sour cherry verticum has been established yet. Most urgent necessity as well as possibility of changes are felt in the Northern Great Plain Region.